2023
DOI: 10.59298/idosrjhss/2023/12.1.5000
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urban Planning on Household Poverty Reduction in Uganda: A Review

Muhwezi Amosi Kahara , Edaku Charles , Asaba Richard Bagonza Grace Lubaale , Val Hyginus Udoka Eze

Abstract: The study analyzed the impact of urban planning on reducing household poverty in Uganda. It found that both negative and positive factors significantly influence household poverty. The study also identified five key factors that contribute to household poverty: social services, research and development, employment, and investment. The findings suggest that urban planners should align their policies with government policies when allocating resources to reduce poverty caused by unplanned urbanization. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It was further reported that financial malpractices increase transaction costs, reduce efficiency, and quality of services and distort the decision-making process. The researcher [54], observed that such malpractices lowered the quality of education by citing an example where schools have dilapidated buildings despite the significant financial efforts made by public authorities and the government to provide each child with his/her learning materials [56] [57]. The researcher in [53] reported that financial misappropriation and misuse distort both the quality and availability of education services and resources.…”
Section: Financial Management and The Learning Environment In Educati...mentioning
confidence: 99%
“…It was further reported that financial malpractices increase transaction costs, reduce efficiency, and quality of services and distort the decision-making process. The researcher [54], observed that such malpractices lowered the quality of education by citing an example where schools have dilapidated buildings despite the significant financial efforts made by public authorities and the government to provide each child with his/her learning materials [56] [57]. The researcher in [53] reported that financial misappropriation and misuse distort both the quality and availability of education services and resources.…”
Section: Financial Management and The Learning Environment In Educati...mentioning
confidence: 99%
“…Regional poverty saw a decline of 1.6% annually, and international poverty decreased by 2.7% per annum, ranking Uganda with the second-fastest poverty reduction rate in Sub-Saharan Africa. However, by 2013, over a third of the population still lived below the international poverty line of US$1.90 a day, showcasing the endurance of poverty despite advancements [4] [1]. Critically, the disparity between Uganda's poverty line in the 1990s and early 2000s and the international poverty line raises questions about the adequacy of Uganda's poverty metrics.…”
Section: Government Interventions and Household Poverty Dynamics In U...mentioning
confidence: 99%
“…This scholarly research review stands at the intersection of policy, economics, and social welfare, delving deep into the heart of Uganda's socioeconomic landscape. As scholars dedicated to unravelling the complexities of poverty alleviation, our pursuit is to meticulously dissect the multifaceted relationship between government interventions and the poverty-stricken households of Uganda [1] [2]. Uganda, a nation marked by its rich cultural heritage and natural diversity, has made significant strides in recent decades, yet challenges persist in the form of widespread poverty that grips a substantial portion of its populace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation